2020
DOI: 10.3390/plants9111577
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antimicrobial and Larvicidal Activities of Green Synthesized Silver Nanoparticles Using Leaf Extract of Plumbago auriculata Lam

Abstract: This work reports the synthesis of silver nanoparticles (AgNPs) using aqueous extract of Plumbago auriculata, and evaluates their antibacterial and larvicidal activities. The synthesized silver nanoparticles were characterized by various spectroscopy techniques, such as FTIR, XRD, TEM, EDX, Zeta potential, and DLS. The synthesized AgNPs exhibited significant antibacterial activity against Gram-positive and Gram-negative bacteria, such as Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Klebsiell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…The size of the green synthesized AgNPs was found nearly similar between the TEM and DLS analysis. The higher negativity value of the zeta potential specified stability and well-dispersed behavior of nanoparticles [ 70 ]. Thus, our results prove the efficacy of components present in the Diospyros malabarica fruit extract as reducing and capping agents for the synthesis of AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the green synthesized AgNPs was found nearly similar between the TEM and DLS analysis. The higher negativity value of the zeta potential specified stability and well-dispersed behavior of nanoparticles [ 70 ]. Thus, our results prove the efficacy of components present in the Diospyros malabarica fruit extract as reducing and capping agents for the synthesis of AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Ekennia, Anthony C., et al reported the formation of spherical silver nanoparticles using Euphorbia sanguinea and its photocatalytic degradation of CR (90% within 1 h) [208]. In the period of 2019-2020, several publications reported Silver nanoparticles synthesized using leaf extract of various plants, e.g., Borago officinalis [209], Tragopogon collinus [210], Melia azedarach [211], Mentha aquatica [212], Ziziphus joazeiro [213], Elytraria acaulis [214], Hyptis suaveolens [215], Caesalpinia pulcherrima [216], Gomphrena globosa [217], Plumbago auriculata [218], Cucumis prophetarum [219], Polygonatum graminifolium [220], Cocos nucifera [221], Mimosa albida [222], Capparis zeylanica [223], Holoptelea integrifolia [224], Annona Reticulatal [225], Combretum erythrophyllum [226], Berberis vulgaris [227], Catharanthus roseus [228], Ganonerion polymorphum [229], Premna integrifolia L [230], and Piper betle [231]. Roots are also well established for the synthesis of silver nanoparticles, as shown in Table 13.…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 99%
“…The produced silver NPs possessed an antioxidant activity and antitumor activity against Dalton's Lymphoma as well as antibacterial activity against Gram-positive and Gram-negative bacteria such as Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Klebsiella pneumonia. They also showed larvicidal activity against Aedes aegypti and Culex quinquefasciatus and antitubercular activity against Mycobacterium tuberculosis [3][4][5][6]. Selenium NPs were previously synthesized by green methods using P. zeylanica extract and found to have an antioxidant and antibacterial activities [7].…”
Section: Introductionmentioning
confidence: 99%